Application of lightning discharge generated radio atmospherics/tweeks in lower ionospheric plasma diagnostics - Maurya, A.K.; Singh, Rajesh; Veenadhari, B.; Pant, P.; Singh, A.K. (My University, 2010)
Lightning discharges during thunderstorm are the significant natural source of electromagnetic waves. They generate electromagnetic pulses, which vary from few Hz to tens of MHz, but the maximum radiated energy is confined in extremely low (ELF: 3-3000Hz) and very low (VLF: 3-30 KHz) frequency band. These pulsed signals with frequency dispersion are known as radio atmospherics or tweeks. These waves propagate through the process of multiple reflections in the earth-ionosphere waveguide over long distances with very low attenuation (2-3 dB/1000km). Since these waves are reflected by lower boundary of ionosphere, these are used extensively for probing the D-region ionosphere. D-region is important to the space weather, as well as the submarine communication and navigational aid. In this perspective the measurement of electron density profiles of the D-region is undoubtedly of great interest to both the development of reliable models and radio wave propagation. Earlier work on the tweeks is mainly focused to the theoretical considerations related to polarization, waveform analysis, and occurrence time and propagation mechanism. In this study we investigate tweeks to determine the equivalent night time electron densities at reflection height of the D-region. Distance traveled by the VLF waves from the causative lightning discharges to the receiving station has also been calculated. Tweeks recorded at a low latitude ground station of Allahabad (Geomag. lat. 16.050 N) during the night of 23 March 2007 have been used in the present analysis. Based on the analysis of the fundamental cut-off frequency of tweeks, the estimated equivalent electron density of the D-region has been found to be in the range of ~20 to 25 el/cm3 at ionospheric reflection height of ~80 to 95 km respectively. Propagation distance in Earth-Ionosphere wave guide (EIWG) from causative lightning source to experimental site varies from ~1500 to 8000 km.
Keywords: Lightning discharges; Electromagnetic waves; D-region; Earth-Ionosphere wave; VLF waves